2017
DOI: 10.1177/2158244017692015
|View full text |Cite
|
Sign up to set email alerts
|

Social Interactions and Cultural Repertoires as Resources for Coping With Breast Cancer

Abstract: The article aims to better understand the role of cultural and social resources for coping with cancer as a disruptive experience. Fourteen women who had recently received a diagnosis of breast cancer and started a treatment in an Italian hospital have been interviewed individually to elicit narratives regarding the interactions with the other patients. The analysis focused on the role played by social interactions and cultural repertoires as devices for making sense of and facing the illness. Results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The family also plays a key role in obtaining informational support, by mediating communication with doctors. Contact with breast cancer patients and survivors is an additional source of supporting information, with however a possible negative impact in terms of emotional coping [17]. Interviewees such as L. deliberately avoided interactions with other patients as a way to protect themselves from making parallels that might harm their hope and psychological well-being.…”
Section: Informational Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The family also plays a key role in obtaining informational support, by mediating communication with doctors. Contact with breast cancer patients and survivors is an additional source of supporting information, with however a possible negative impact in terms of emotional coping [17]. Interviewees such as L. deliberately avoided interactions with other patients as a way to protect themselves from making parallels that might harm their hope and psychological well-being.…”
Section: Informational Supportmentioning
confidence: 99%
“…Al-Azri et al [10] documented that in lower-income countries women with breast cancer are at an increased risk of physical and psychological morbidities after diagnosis, such as distress, anxiety, depression and concerns relating to children and family burden, body image and sexual and marital relations [11,12]. However, social barriers and the false beliefs about cancer and its association with death for many society members affect a patient's daily life even by avoiding mentioning its name or talking about topics related to the disease [12][13][14][15][16][17][18][19][20][21]. In addition, several studies have showed that in the Arab and Palestinian society, a powerful social stigma is still attached to cancer [13,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Such shared knowledge may not be taken for granted in conversational exchanges wherein participants come from different cultural or linguistic background, as in interactions between ethnically-discordant participants (Penner et al, 2013). Studies on intercultural healthcare settings report general difficulties in communication and mutual understanding between doctors and non-native patients, bearing short-and long-term negative effects on the therapeutic outcomes (Zucchermaglio and Alby, 2017;Almuhtaseb et al, 2020;Dovidio et al, 2016;Maina et al, 2018).…”
Section: Identity Categorisation In Intercultural Medical Encountersmentioning
confidence: 99%
“…Cultural contexts in which individuals are socialized affect the ways they choose or adhere to different coping strategies. Several studies have demonstrated the role of cultural repertoires in the choice of coping strategies to face a difficult crisis such as being struck by cancer (e.g., Kayser et al 2014;Zucchermaglio and Alby 2017).…”
Section: Introductionmentioning
confidence: 99%